A dispermic chimerism detected in a Taiwanese potential unrelated hematopoietic stem cell donor. (February 2017) - Yang, E. K. L.; Marsh, S. G. E.; Chen, P.‐Y.; Chen, C.‐P.; Chen, S.‐P.; Lin, P. Y.
Abstract : Chimerism is defined as the presence of 2 or more than 1 genetically distinct cell populations in an organism. Dispermic chimeras are derived from the fertilization of 1 or 2 matured nuclei by 2 sperms. We here report detection of a healthy and phenotypically normal female with normal ABO red blood cell typing in whom dispermic chimerism was suspected after 3 alleles were identified at multiple human leukocyte antigen (HLA) loci using molecular HLA analysis. Molecular HLA typing showed the donor to have 3 HLA‐A, ‐B, ‐C, ‐DRB1, ‐DQB1 and ‐DPB1 alleles in blood, saliva and nail samples. In addition, 3 of her 9 short tandem repeat loci also showed to have 3 distinct alleles in blood, nail and saliva specimens. In all investigations, the third alleles were attributed to a dual paternal contribution. This case represents a dispermic chimerism, with 2 paternal and 1 maternal haplotypes variably distributed throughout body tissues in a healthy and phenotypically normal female without abnormalities in erythrocyte ABO blood group. The origin of this chimerism is probably due to the fertilization of a single egg and its polar body, or a parthenogenetic egg, by 2 sperms.